Impact of Antenatal Steroid Treatment on External Morphological Feature of Newly Born Rats - A. Salman, Rasha; Rashid Kamoona, Huda; Soussi, Ahlem (Al-Nahrain Journal of Science, 2025)
This paper is about the application of Steroid treatment during pregnancy as practiced in common in practice, in rheumatological and autoimmune diseases, its prolonged use has an adverse effect on fetal growth. The study aimed to assess the effect of prenatal dexamethasone and hydrocortisone treatment on rats’ offspring concerning growth parameters, congenital malformation, and survival rate. Sixty pregnant rats were allocated into 12 groups, and administered intraperitoneally either dexamethasone (1mg/kg/day) or hydrocortisone (9 mg/kg/day), and a control group that received normal saline. These were administered in the first week or last week of gestation. Neonatal body weight, length, and gross morphological anomalies were evaluated postnatal at 1 and 15 days. Prenatal dexamethasone treatment in late pregnancy resulted in 27 % neonatal mortality on day 3. Dexamethasone and hydrocortisone significantly reduced body weight and length of neonates compared to the control group, which is more prominent in dexamethasone treatment. However, both glucocorticoids resulted in profound developmental deficits when given in late pregnancy, especially dexamethasone, which causes profound growth retardation and teratogenic effects in neonates. At the same time hydrocortisone has a less severe impact on postnatal malformations and growth retardation. This sheds more light on the timing of steroid administration during the prenatal period, which should be taken into consideration for risk-benefit assessment.